PROSEDUR PERHITUNGAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 21 ATAS GAJI PEGAWAI PEMERINTAH KABUPATEN MINAHASA SELATAN - Mandak, Andre; Morasa, Jenny (GOING CONCERN : JURNAL RISET AKUNTANSI, 2015)
Income tax (VAT) of article 21 is a tax on income in the form of salaries, wages, fees, allowances, and other similar remuneration derived by any individual taxpayer in respect of employment or office, services, and activities. The purpose of this study is to provide an explanation of the implementation of the calculation and deduction, income tax reporting section 21 and the amount of income tax revenue has been recapitulated by the Government of South Minahasa District. This study used a descriptive analysis method by comparing theory and rules perpajakn there with the data obtained. From the research, it was found the procedure of calculation and reporting of income tax article 21 in the South Minahasa District Government has been good. It can be seen from the calculation until the reporting mechanism has been carried out based on the rules that apply. The use of services and applications for the calculation of Income Tax Article 21 of the PT. TASPEN in connection with the cooperation with the Government of South Minahasa.